Transition‐Metal‐Free Approach for the Direct Arylation of Thiophene: Experimental and Theoretical Investigations towards the (Het)‐Aryne Route. Issue 2 (29th November 2018) - Demangeat, Catherine; Saied, Tarak; Ramozzi, Romain; Ingrosso, Francesca; Ruiz‐Lopez, Manuel; Panossian, Armen; Leroux, Frédéric R.; Fort, Yves; Comoy, Corinne
Abstract : This paper presents the results of our investigations on the arylation of thiophene using the transition‐metal‐free "aryne coupling" methodology. The reaction was studied by both experiment and computation (density functional theory) and comparison with phenyllithium was established. In parallel, the effects of the ligand and the salt on the coupling reaction were examined. The results underline the remarkable effect of such additives on the coupling reaction and the potency of the method to construct hetaryl–aryl backbones which open up promising access to a wide range of heterobiaryl structures using the novel "Het‐Aryne" route. Abstract : The transition‐metal‐free "Aryne coupling" methodology was studied by both experiment and density functional theory. The effects of the ligand and the salt on the coupling reaction were also examined. The method is effective in constructing hetaryl–aryl backbones which open up promising access to a wide range of heterobiaryl structures using the novel "Het‐Aryne" route.